2001
DOI: 10.1046/j.1365-2133.2001.04034.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and polymerase chain reaction typing of Borrelia afzelii from a skin lesion in a seronegative patient with generalized ulcerating bullous lichen sclerosus et atrophicus

Abstract: A 64-year-old woman presented with bullous and ulcerating lichen sclerosus et atrophicus (LSA) on the neck, trunk, genital and perigenital area and the extremities. Histology of lesional skin showed the typical manifestations of LSA; in one of the biopsies spirochaetes were detected by silver staining. Despite treatment with four courses of ceftriaxone with or without methylprednisone for up to 20 days, progression of LSA was only stopped for a maximum of 1 year. Spirochaetes were isolated from skin cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 40 publications
(78 reference statements)
3
38
0
2
Order By: Relevance
“…Reactivation of infection during this culture-negative state obviously occurs spontaneously or following immunosuppression after the conclusion of treatment. Such reactivation is similarly documented for LB and syphilis [12,14,54,67,76]. In addition, B. burgdorferi s.l.…”
Section: Are There Clinically Relevant Differences In the Antimicrobimentioning
confidence: 60%
“…Reactivation of infection during this culture-negative state obviously occurs spontaneously or following immunosuppression after the conclusion of treatment. Such reactivation is similarly documented for LB and syphilis [12,14,54,67,76]. In addition, B. burgdorferi s.l.…”
Section: Are There Clinically Relevant Differences In the Antimicrobimentioning
confidence: 60%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] A bacterial cause was further suggested because several cases of LS responded well to therapy with antibiotics, such as dirithromycin, penicillin, and ceftriaxone. 20,36,37 In the present study, we detected B burgdorferi sensu lato in more than 60% of all LS cases, with a significantly higher percentage (P=.001) in early (80%) than in late (33%) LS, while it made no difference whether LS was associated with morphea. This might reflect intentional or coincidental antibiotic exposure in longerterm cases and/or the natural course of disease, with repression of the microorganism by the immune system.…”
Section: Commentmentioning
confidence: 99%
“…Studies reporting a positive association between B burgdorferi infection and LS found evidence of the organism in 10% to 68% of cases; on the other hand, there are reports in which no positive cases could be identified ( Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20] One main difficulty in assessing the association between LS and borreliosis is the…”
mentioning
confidence: 99%
“…Als Ursachen werden unter anderem eine Borreliose [4,5], Hepatitis C [6], Störungen der Androgenregulation, Autoimmunprozesse sowie genetisch determinierte Anfälligkeit [7] diskutiert. Eine retrospektive Studie zeigte beim Lichen sclerosus der Vulva eine Assoziation mit Autoimmunerkrankungen, vor allem aber in einem Großteil der Fälle mit einer positiven Familienanamnese für einen Lichen sclerosus [1].Auch wird über die Induktion eines Lichen sclerosus et atrophicus durch Strahlentherapie berichtet [8].…”
Section: äTiologie Und Pathogeneseunclassified